Sorption of surfactants on silica gel in conditions of ascending thin-layer chromatography with micellar mobile phases - Loginova, L.P.; Yedamenko, D.V. (Functional Materials, 2014)
The paper is devoted to estimation of the presence of micellar front on the plates with polar sorbent. It has been found that at elution by solutions of CPC and non-ionogenic Twin-80 on the plates with polar silica gel three fronts are formed: first one is visually observed front of solvent; second one is observed at UV-irradiation and corresponds to the water solution of surfactant monomers and third one corresponds to micelles of surfactant and is observed at erythrosine staining. The received results permit to describe the mechanism of chromatographic separation of analytes, which differs from the mechanism in micellar TLC with an non-polar stationary phase. It was shown that the process of separation of substances with micellar mobile phase is complex from the viewpoint of mechanism of separation: while initially substance is separated within three-phase system, finally it became separated within two-phase system.